Agroforestri: Inovasi Hijau dalam Upaya Mitigasi Perubahan Iklim di Desa Andalambe Kecamatan Tongauna Utara Kabupaten Konawe - Erif, La Ode Muhammad; Gandri, La; Sudia, La Baco; Indriyani, Lies; Kahirun, Kahirun; Siwi, La Ode; Teke, Junartin; Tuwu, Eka Rahmatiah; Midi, La Ode; Hidayat, Herlan; Fitriani, Vivi (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2025)
Andalambe Village, North Tongauna Sub-district, Konawe Regency, is facing the impacts of climate change affecting the agricultural sector, particularly due to erratic droughts and floods. This causes a decrease in agricultural productivity and risks threatening community food security. This community service aims to empower farmers through the application of biopore technology and agroforestry patterns as a solution for water conservation and increasing agricultural resilience to climate change. The methods used include socialization on the impacts of climate change, training, and hands-on practice of making biopore holes and implementing agroforestry systems. The results of the activities show that farmers can adopt this technology well. Biopore pits are proven to increase water absorption, reduce the risk of flooding, and maintain water availability during the dry season. Meanwhile, agroforestry contributes to improving soil fertility and enriching agricultural ecosystems. The application of these two technologies not only increases agricultural productivity but also strengthens food security and the community's adaptive capacity to environmental change. The sustainability of this program is expected to support the long-term stability of agricultural production and the welfare of farmers in Andalambe Village.